Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex](49^x)(7 ^{x^2})=2401^2 \\ \\( (7^2)^x)(7 ^{x^2})= (7^4) ^2 \\ \\ 7 ^{2x}\cdot 7^{x^2}=7^{8} \\ \\ 7 ^{2x+x^2} =7^{8} \\ \\2x+x^2 =8[/tex]
[tex]x^2-2x-8 = 0\\ \\ a=1, \ b=-2, \ c=-8 \\ \\\Delta =b^2-4ac = (-2)^2 -4\cdot1\cdot (-8) = 4 +32 =36 \\ \\x_{1}=\frac{-b-\sqrt{\Delta} }{2a}=\frac{2-\sqrt{36}}{2 }=\frac{ 2-6}{2}=\frac{-4}{2}=-2 \\ \\x_{2}=\frac{-b+\sqrt{\Delta} }{2a}=\frac{2+\sqrt{36}}{2 }=\frac{ 2+6}{2}=\frac{8}{2}= 4 \\ \\Answer: \ x=-2 \ \ or \ \ x=4[/tex]
[tex]x^2-2x-8 = 0\\ \\ a=1, \ b=-2, \ c=-8 \\ \\\Delta =b^2-4ac = (-2)^2 -4\cdot1\cdot (-8) = 4 +32 =36 \\ \\x_{1}=\frac{-b-\sqrt{\Delta} }{2a}=\frac{2-\sqrt{36}}{2 }=\frac{ 2-6}{2}=\frac{-4}{2}=-2 \\ \\x_{2}=\frac{-b+\sqrt{\Delta} }{2a}=\frac{2+\sqrt{36}}{2 }=\frac{ 2+6}{2}=\frac{8}{2}= 4 \\ \\Answer: \ x=-2 \ \ or \ \ x=4[/tex]
[tex](49^x)(7^{x^2})=2401^2\\ \\7^{2x} \cdot7^{x^2}=(7^4)^2\\ \\7^{2x+x^2}=7^8\ \ \ \Leftrightarrow\ \ \ 2x+x^2=8\ \ \ \Leftrightarrow\ \ \ x^2+2x-8=0\\ \\x^2-2x+4x-8=0\ \ \ \Leftrightarrow\ \ \ x(x-2)+4(x-2)=0\\ \\(x-2)(x+4)=0\ \ \ \Leftrightarrow\ \ \ ( x-2=0\ \ \ \vee\ \ \ x+4=0)\\.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=2\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=-4[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.